Small non-coding RNAs encoded by RNA viruses: old controversies and new lessons from the COVID-19 pandemic - Ruivinho, Carolina; Gama-Carvalho, Margarida (Frontiers in Genetics, 2023)
The recurring outbreaks caused by emerging RNA viruses have fostered an increased interest in the research of the mechanisms that regulate viral life cycles and the pathological outcomes associated with infections. Although interactions at the protein level are well-studied, interactions mediated by RNA molecules are less explored. RNA viruses can encode small non-coding RNAs molecules (sncRNAs), including viral miRNAs (v-miRNAs), that play important roles in modulating host immune responses and viral replication by targeting viral or host transcripts. Starting from the analysis of public databases compiling the known repertoire of viral ncRNA molecules and the evolution of publications and research interests on this topic in the wake of the COVID-19 pandemic, we provide an updated view on the current knowledge on viral sncRNAs, with a focus on v-miRNAs encoded by RNA viruses, and their mechanisms of action. We also discuss the potential of these molecules as diagnostic and prognostic biomarkers for viral infections and the development of antiviral therapies targeting v-miRNAs. This review emphasizes the importance of continued research efforts to characterize sncRNAs encoded by RNA viruses, identifies the most relevant pitfalls in the study of these molecules, and highlights the paradigm changes that have occurred in the last few years regarding their biogenesis, prevalence and functional relevance in the context of host-pathogen interactions.